Procedural Change in the UK House of Commons, 1811-2015 - Goet, ND; Fleming, TG; Zubek, R (Wiley, 2019)
Recent research has shown an increasing interest in the historical evolution of legislative institutions. The development of the UK Parliament has received particularly extensive attention. In this article, we contribute to this literature in three important ways. First, we introduce a complete, machine-readable data set of all the Standing Orders of the UK House of Commons between 1811 and 2015. Second, we demonstrate how this data set can be used to construct innovative measures of procedural change. Third, we illustrate a potential empirical application of the data set, offering an exploratory test of several expectations drawn from recent theories of formal rule change in parliamentary democracies. We conclude that the new data set has the potential to substantially advance our understanding of legislative reforms in the United Kingdom and beyond.